Neuroimaging Findings in Griscelli syndrome: A case report and review of the literature - Alsugair, Faisal (Radiol Case Rep, 2020)
Our case involved a 1-year-old female with multiple admissions for chest infections. Given her family history and high clinical suspicion, a diagnosis of Griscelli syndrome and hemophagocytic lymphohistiocytosis was made. Her work-up included a brain MRI, which revealed diffuse volume loss and corpus callosum hypogenesis associated with a diffuse simplified pattern of the sulci and gyri compatible with lissencephaly. We describe hypogenesis of the corpus callosum and lissencephaly for the first time in this syndrome.